A comparison of nearby incremental ground level and in plant concentrations of air pollutants emitted from electronics facilities - P. L., Law; S. C., Gracie Chong; A., Baharun; A., Abdul Rahman (Springer-Verlag, 2006)
Air dispersion modeling by was recently conducted to predict the incremental ground level and inplant concentrations of toxic organic chemicals due to stack and fugitive emissions from Sama Jaya Free Industrial Zone (SJFIZ), Kuching, Sarawak, Malaysia. Simulations of organic air pollutants emitted from industrial facilities in SJFIZ from years 1996 to 2001 were carried out in September 2004 by members of Faculty of Engineering, Universiti Malaysia Sarawak (UNIMAS). The results indicated that there were negligible amount of maximum incremental ground level concentrations of less than 3x10-2 μg/m3 for 365-day average, and less than 18x10-2 μg/m3 for 24 h. average. For in-plant maximum incremental concentrations, it is found that the simulated results were much lower than TWA values, except xylene. The predicted in plant concentration of xylene was 119.21 (parts per million) ppm as compared to ACGIH TLV-TWA of 100 ppm approximately 19% higher than ACGIH recommended values. From this study, it was concluded that both nearby population and in plant workers were not potentially at risk to exposing organic chemicals far lower than the threshold limit levels set by ACGIH.